On The Partially Reacted Boundary Layer in Rate Sticks - Partom, Yehuda (European Journal of Applied Sciences, 2023)
Using our temperature dependent reactive rate (TDRR) reactive flow model to simulate detonation in a rate stick, we observe that a partially reacted layer (PRL) is being formed near the boundary. We are not aware that such a PRL has been observed in tests, and this is why we regarded it in the past as a numerical artifact. Assuming that such an artifact may be caused by the finite rise time of the detonation shock, we showed in [1] how it can be eliminated by delaying the outward boundary motion for a length of time comparable with the shock rise time. Here we revisit the PRL problem. We first show that it is not a numerical artifact but a real phenomenon. We do this by repeating the reactive flow run with a finer mesh. By looking at the PRL structure, we see that doubling the resolution affects the PRL only slightly. We then conjecture that the PRL formation has to do with the finite duration of the reaction process (or the finite extent of the reaction zone). By the time the boundary rarefaction reaches a cell near the boundary, it may still be only partially reacted, and its reaction process may be therefore cut off. To establish our conjecture, we show how the PRL structure changes with the reaction duration.